Consolidation characteristics of Pathumwan clay - Boonthep Nanegrungsunk; Brenner, R.P.; Brand, E.W.; Holmberg, Soren; The government of the Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1976)
Four series of consolidation tests were carried out on soft, medium, and stiff Bangkok clay from boreholes at Chulalongkorn Campus and Lumpini Park in order to investigate maximum past pressures, compressibility characteristics, effect of sample size and influence of load increment ratio and load increment duration. Tests were carried out in lever-arm type oedometers as well as in hydraulic oedometers with pore pressure measurement. Sample sizes varied between 2.5 and 6 inches. A series of piezometers were also installed near the borehole at Chulalongkorn Campus. Maximum past pressures were determined by applying small load increments and fairly accurate values could be obtained. Samples from both boreholes showed the same consolidation characteristics. The transition from medium to stiff clay took place at a depth between 12.5 and 13.5 m. The compressibility values, av & mv of medium clay were about 2.5 times greater than those of stiff clay in the pressure range straddling the preconsolidation pressure. The effect of sample size on av, mv, cv and Cc as well as the time for 100% pore water dissipation appeared to be insignificant. The effect of load increment ratio on .secondary compression characteristics such as Rs (coefficient of secondary compression), Rs/6p (rate of secondary compression) and Rs/6p~H (secondary compressibility) .was found to be insignificant for 6 inch diameter samples. The piezometers installed recorded a significant pressure deficiency below 18.5 m. There the measured pressure head was about 12 m lower than the corresponding hydrostatic head.
A thesis submitted in partial fullfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Clay -- Thailand -- Pathumwan -- Testing